What to Look for in Relationships: Development, inter-rater reliability, and initial validity estimates for a young child-caregiver relationship assessment - Osofsky, Joy D.; Fields-Olivieri, Margaret A.; Frazer, Andrew L.; Graham, Rebecca A.; McCurdy, Bethany H.; Weems, Carl F. (Frontiers in Psychology, 2023)
Introduction Observational assessments are important for understanding a range of behaviors and emotions in the young child-caregiver relationship. This paper provides initial data on a multidimensional assessment for professionals who work with young children and their caregivers, the What to Look for in Relationships (WLR). The WLR was designed to assist providers in evaluating strengths and areas for improvement in five areas of young child-caregiver relationship dimensions. This paper reports on the development, interrater reliability, initial convergent and discriminant validity, and incremental utility of the scales. Methods Data were collected from caregiver-child dyads, who participated in a semi-structured observational caregiver-child interaction session as part of a clinic evaluation for relationship-based therapeutic services for young children in child protection. Recorded interactions were coded using the WLR scales with 146 interactions coded by at least two independent observers for interrater reliability analyses. Results The scales showed adequate internal consistency, good inter-rater reliability, strong convergent associations with a single dimension measure (i.e., the Parent-Infant Relationship Global Assessment Scale; PIR-GAS) and discriminated those in the clinical range from those with adaptive functioning on the PIR-GAS. Discussion This study provides initial support for the usefulness of the WLR scales for assessing dimensions of caregiver-child relationships during early childhood that may be useful targets of intervention.